Analyzing multi-mode and multi-position reliability of composite reinforced plate based on branch-bound method - FENG Yunwen; SONG Zhicen; CAO Yizhe; LU Cheng; XUE Xiaofeng (Xibei Gongye Daxue Xuebao)
To overcome the concurrency of multi-mode and multi-position failures of composite structures, this paper explores the application of the branch-bound method (BBM) to the multi-mode and multi-position reliability analysis and combines the Monte Carlo method to solve the multi-mode reliability. Firstly, "branch" is carried out by combining structural composition with loading state to identify all possible potential failure modes; "boundary" is carried out by combining structural characteristics with stress state to determine main failure modes and failure positions, thus establishing a multi-mode reliability analysis model. Secondly, by translating the unequal failure criterion to safe boundary equations, a framework for the reliability analysis of composite materials was established, and the Monte Carlo method was used to solve the reliability of multi-mode and multi-position failures. Finally, a reliability analysis case was used to validate the composite T-type reinforced plate under axial compressive load. The use of the BBM reduces the computational scale by 75%. The multi-mode reliability of the reinforced plate under axial compressive load is 0.998.